The Challenges of Military Operations in Plateau State, North-Central Nigeria, 1999 To 2022. - Okene , Adams Ahmed; Itodo , Felicia (Corpus Intellectual, 2025)
Plateau State has been engulfed in lots of security challenges for about two decades now which made the erstwhile peaceful state a theatre for ethno-religious tensions. The constant resurgence of this security challenge in the state necessitated the deployment of the military to Plateau State to provide security and ensure peace in the state. The paper deployed the historical tools of research which include primary and secondary materials such as oral interviews, reports, journals amongst others. However, the military operations in the State have suffered several challenges and chief amongst these challenges is the bias and perception held by the people of Plateau on the non- neutrality of the military in its operations on the Plateau. This paper therefore examines this alleged bias of the military in its operations. The paper argues that the seemingly bias of military operations in the state is not an institutional objective of the military but stems from its challenges on securing the Plateau because the military is a disciplined institution where the spirit of camaraderie is very high. Thus, the issue of the military being partisan along ethno-religious lines in the Plateau security challenges is unfounded. The paper further argues that this trust deficiency between the military and the people could mar the success of confronting the security challenges in Plateau state and recommends trust building, open communication amongst others.